УЛЛЫ ЖИПЕК ЖОЛЫНДАҒЫ АРАЛ БОЙЫ ҚАЛАЛАРЫНЫҢ САЎДА ҲӘМ МӘДЕНИЙ БАЙЛАНЫСЫ - Акимниязова, Г. (FAN va JAMIYAT, 2016)
The article deals with the questions of the directions of trade ways, trade-economic and cultural relationship, origin of towns, caravan-shed, signal towers on the route Great Silk Road and on the Plateau Ustyurt. The written sources have been used in the work.